DO DEMAND SIDE POLICIES IMPROVE THE FOOD SECURITY OF LANDLESS RURAL HOUSEHOLDS? INVESTIGATING PAKISTAN’S ACHIEVEMENTS IN THE PUNJAB - M. K. Bashir; S. Schilizzi; S. Mohammad (Journal of Animal and Plant Sciences, 2014)
The study aims to assess the impact of two short term demand-side policies on the food security of landless rural households. A conceptual model is designed to work out the policy impact pathways using a partial equilibrium technique. Primary data from 576 landless rural households was analyzed using a two-stage (fold) regression model. The first stage of the analysis shows that food subsidies significantly improve food intake along with monthly income, livestock assets (large animals) and household heads’ education The second stage shows that monthly income increases due to the minimum wage rate, joint family system, livestock assets (large animals), and education level of intermediate and graduation.
Keywords: Demand-side policies; impact assessment; rural food security; landless households; Punjab; Pakistan